Conversion of Organic Matter of Carbonate Deposits in the Hydrothermal Fluid - Sergey M. Petrov (MDPI AG, 2021)
This present paper investigates the conversion of organic matter in carbonate rocks of the Semiluksko-Mendymsky horizon Volga-Ural Basin under hydrothermal conditions with excess water in subcritical conditions at 613–653 K and 170–200 Bar. It has been found that the content of hydrocarbon extracts increases (relatively) which indicates the oil-generating potential of the studied deposits. Besides, it has been shown that organic matter undergoes oxidation reactions under hydrothermal conditions, as indicated by the presence of oxidized structures in the extracted hydrocarbons. Moreover, our results indicate that increasing the temperature and pressure of the used hydrothermal fluid leads to an increase in the content of n-alkanes C25-C30 and asphaltenes in the extracts. On the other hand, it has been found that saturated, aromatic hydrocarbons and resins content decreases at this stage. The obtained data about the geochemical parameters dependencies of the hydrocarbons obtained from the studied carbonate rock on temperature and pressure associated to hydrothermal effect show possible pathways of migration, genesis, and formation of hydrocarbon deposits.